Developing Sangiran Archaeological Site as Tourism Destination: Social Expectations and Governmental Policy’s Constraints - Basuki Agus Suparno; Kurnia Arofah; Isbandi Sutrisno (Journal of Indonesian Tourism and Development Studies, 2021)
Sangiran is an archaeological site that was established as a cultural heritage by Indonesia and was recognized as a world cultural heritage by UNESCO. Since the 1930s, Sangiran local people have become familiar with the visitors who investigate the site. In 2009, Ministry of Education established Sangiran Primordial Human Conservation Centre (Balai Pelestarian Manusia Purba Sangiran - BPSMPS). Later in 2010, the Indonesian government released the Law 2010/No. 11 about Cultural Heritage for all Cultural Heritage around Indonesia. Both BPSMPS and the law bring changes in Sangiran. This research aims to expose the social expectation and governmental policy constraints after the BPSMPS and the Law 2010/No 11 has been implemented for 10 years. This research was conducted by critical ethnography. Findings of this research are, a) Sangiran local people feel disadvantages and distrust by the implementation of Cultural Heritage Law, yet they adapt and obey the law; b) two expectations should be synchronized, on one other side, the first tourism development must be accelerated, and the second is the implementation conservation principle must be reinvented; c). clear policy related to every stakeholder's roles must be formed to avoid sectoral ego and clash among stakeholders. It must be secured and maintain to synergize to any kind of resources there.Keywords: Conservation, cultural heritage law, heritage tourism, Sangiran, social expectation.